Juridical Review of Citizen Lawsuit in its Application in Indonesia - Ermania Chobelia Fitriana; Nabilla Farah Quraisyta (RIRAI Publisher, 2022)
In Indonesia, there are people who feel that the fulfillment of public facilities provided by the government has not been fully fulfilled. This has an impact on the disappointment of the people who feel that their rights have only been violated or not fulfilled by the government. The community then files a lawsuit to the Court using the Citizen lawsuit method Lawsuits. Many of these lawsuits were rejected by the courts because they were deemed not to meet the elements of the Citizen Lawsuit . Citizen Lawsuit is a citizen's right to sue which is intended to protect citizens from various losses due to actions, policies or decisions made by the Government. Although b many lawsuits are filed using the Citizen Lawsuit method but there are no laws and regulations governing the lawsuit that . This study aims to describe and analyze questions about what elements must be met so that a lawsuit is categorized as a lawsuit Citizen Lawsuit and Position Citizen Lawsuit in civil procedural law in Indonesia . The research method used was collected using normative research techniques and then analyzed qualitatively , namely an analysis that describes the data obtained in the form of sentence descriptions. Then a conclusion is drawn which is the answer to the problem. It is hoped that in the future there will be a definite rule regarding the model of the Citizen Lawsuit lawsuit in Indonesia, as well as the rules regarding Class Action and Legal Standing